2012
DOI: 10.1074/jbc.m112.372151
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Partitioning between Synthetic and Editing Pathways in Class I Aminoacyl-tRNA Synthetases Occurs at Both Pre-transfer and Post-transfer Hydrolytic Steps

Abstract: Background: Error-prone aminoacyl-tRNA synthetases clear noncognate aminoacyl-adenylates and misacylated tRNAs within synthetic and editing sites, respectively. Results: Product release limits the rate of post-transfer editing by leucyl-tRNA synthetase. Conclusion: Kinetic partitioning of misacylated tRNA determines the relative contribution of cis and trans editing. Significance: In contrast to DNA polymerases, error correction in class I tRNA synthetases relies on substrate selection by the editing site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
121
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(134 citation statements)
references
References 72 publications
12
121
1
Order By: Relevance
“…Structural and kinetic analyses revealed that the large peptide fragment (connective peptide, CP1), inserted into the Rossmann fold catalytic domain, folds into a well defined domain dedicated to post-transfer editing (21)(22)(23)(24). IleRS shares this feature with homologous class Ia leucyl-and valyl-tRNA synthetases (LeuRS and ValRS, respectively) (25)(26)(27). Along with deacylation of valyl-tRNA Ile (Val-tRNA Ile ) at the CP1 domain, IleRS also displays a distinctive capacity to hydrolyze valyl-AMP in a tRNA-dependent manner within the synthetic site (12,28).…”
mentioning
confidence: 99%
“…Structural and kinetic analyses revealed that the large peptide fragment (connective peptide, CP1), inserted into the Rossmann fold catalytic domain, folds into a well defined domain dedicated to post-transfer editing (21)(22)(23)(24). IleRS shares this feature with homologous class Ia leucyl-and valyl-tRNA synthetases (LeuRS and ValRS, respectively) (25)(26)(27). Along with deacylation of valyl-tRNA Ile (Val-tRNA Ile ) at the CP1 domain, IleRS also displays a distinctive capacity to hydrolyze valyl-AMP in a tRNA-dependent manner within the synthetic site (12,28).…”
mentioning
confidence: 99%
“…In many cases, this activity seems to be enhanced in the presence of tRNA (20,21,23). Thus, in the evolution of LeuRS, IleRS, and ValRS, the original insertion of the CP1 domain likely affected fidelity via a set of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The balance of fidelity mechanisms that rely on post-or pretransfer editing can differ and shift (8,25). A preponderance of posttransfer editing versus pretransfer editing can be dictated by a rapid aminoacyl-transfer step in the aminoacylation site (22,23,41). Likewise, the CP1 domain in IleRS relies upon pretransfer editing as its dominant editing pathway (42) because of a slow transfer rate (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, our comprehensive work on the mechanism of pre-transfer editing proved the model wrong and demonstrated that pre-transfer editing reactions actually reside within the confines of the synthetic site. [48][49][50][51][52] SerRS was the highly important player in establishing this new pre-transfer editing model. as this enzyme, in all domains of life, naturally lacks a domain specialized in editing.…”
Section: Serrs: a Proofreading Enzyme Without The Error-correction Domentioning
confidence: 99%